DISTORTION OF TRADERS' BEHAVIOR IN THE PERSPECTIVE OF SHARIA ECONOMICS : (CASE STUDY ON THE TRADITIONAL MARKET OF APALA DISTRICT, BAREBBO DISTRICT) - Niar, Kasriani -; HAMZAH, AKSI; HASNI, HASNI (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This research aims to determine the distortion of trader transaction behavior in the market, determine customer perceptions of the distortion of trader transaction behavior and to determine the sharia economic perspective on the distortion of trader behavior and customer perception in the traditional market of Apala District. Barebbo. This research is field research whose research approach is a qualitative approach. The types of data used in this research are primary data and secondary data. Data analysis techniques are data reduction, data presentation and drawing conclusions. The results of this research reveal a positive picture regarding trader transaction behavior at the Apala market. There is no evidence of hoarding of goods which shows transparency in the supply of goods. However, there is still a tendency for unfair pricing, indicating the need for stricter market regulations. Other findings highlight a reduction in the quantity of goods and deficiencies in the quality of goods. However, the research results also illustrate that the relationship between traders and customers tends to be positive.